Fizikalne knjige v Turjaški knjižnici - Južnič, Stanislav (Knjižnica, 2006)
The early decades of the Auersperg Princes' Library of Ljubljana are described. The special concern is put on the Count Volf Engelbert's and his brother Prince Janez Vajkard's scientific opinions at the mid-17th century. The catalogue of Auerspergs' philosophy-physics books has been researched. The importance and value of particular items is discussed in the light of old fashion Aristotelian physics of their student days, the influences of: Protestants which they both belonged to until their teenage years; the monks of different orders; the modern Academicians, especially Galileo's dei Lincei; and the magicians as predecessors of modern science. The Library has been used as the basis for the analysis of Auerspergs' early modern interests just after they returned to the Catholic faith. Some books of the former Ljubljanian library could be traced in different libraries in USA and Europe. The Auerspergs' library has been compared with other similar European 17th century libraries.
Keywords: zasebne knjižnice; knjižnični fondi; philosophy; filozofija; fizika; physics; Turjačani; Auerspergi(rodbina); zgodovinski pregledi